2019
DOI: 10.1002/jcla.22873
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of HOXA9 promoter hypermethylation in head and neck squamous cell carcinoma

Abstract: BackgroundThe purpose of the current study was to assess the association between HOXA9 (homeobox A9) promoter methylation and head and neck squamous cell carcinoma (HNSCC) and its diagnostic value.MethodsQuantitative methylation‐specific PCR (qMSP) was applied to measure HOXA9 promoter methylation levels in 145 paired HNSCC and corresponding normal tissue samples. Data from the Cancer Genome Atlas (TCGA) database (n = 578; 528 HNSCC and 50 normal) were also analyzed.ResultsSignificantly higher levels of HOXA9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Abnormal expression of HOXA9 is associated with the occurrence of a variety of cancers [20][21][22]. Several recent studies have shown that hypermethylation of the HOXA9 promoter causes transcriptional inactivation in many malignant tumors [23][24][25]. In our study, INHBB and HOXA9 were hypermethylated in patients with obesity.…”
Section: Discussionsupporting
confidence: 56%
“…Abnormal expression of HOXA9 is associated with the occurrence of a variety of cancers [20][21][22]. Several recent studies have shown that hypermethylation of the HOXA9 promoter causes transcriptional inactivation in many malignant tumors [23][24][25]. In our study, INHBB and HOXA9 were hypermethylated in patients with obesity.…”
Section: Discussionsupporting
confidence: 56%
“…We may conclude that the difference in the DNA methylation pattern of a significant number of genes that we described should be discriminative enough for diagnostics of SE versus NS similar to that recently proposed for lung adenocarcinoma where the methylation in HOXA9 was upregulated in contrast to its downregulation in other three genes [ 56 ]. Importantly, microRNAs of the miR-371-373 cluster that were found in patients with germ cell tumors (GTCs) and even in experimental teratomas derived from human genetically modified stem cells in the teratoma assay that should be devoted not only to the confirmation of pluripotency but also to the possible malignancy of such cells [ 57 , 58 ] have lately been intensively investigated for liquid biopsies and early diagnostics of TGCT, but they do not discriminate between SE and NS as did our results with promoter methylation.…”
Section: Discussionsupporting
confidence: 74%
“…Among HOXB genes, HOXB13 is frequently identified as being hypermethylated in tumors. Its promoter methylation is a candidate biomarker for gastric [64] and endometrial tumors with enhanced invasiveness [114]. The hypermethylation of HOXB13 also occurs in nearly 30% of renal cell carcinomas, as the silencing of this gene is associated with apoptosis ratio decrease, tumor grade increase and microvessels invasion [61].…”
Section: Hoxb and Hoxc Genes Methylated In Cancermentioning
confidence: 99%